Anticancer activity of a cis-dichloridoplatinum(ii) complex of a chelating nitrogen mustard: insight into unusual guanine binding mode and low deactivation by glutathione. Issue 8 (26th January 2016) - Karmakar, Subhendu; Purkait, Kallol; Chatterjee, Saptarshi; Mukherjee, Arindam
Abstract : A platinum(ii ) complex (2 ) of a chelating nitrogen mustard shows potency against MIA PaCa2.2 displays anti-angiogenic potential and displays excellent cytotoxicity profile even in presence of GSH in hypoxia. Abstract : A pyridine ring containing a chelating nitrogen mustard ligand bis(2-chloroethyl)pyridylmethylamine hydrochloride (L2 ·HCl) was synthesized from bis(2-hydroxyethyl)pyridylmethylamine (L1 ) on reaction with thionyl chloride. Both the ligands upon reaction with cis -[PtCl2 (DMSO)2 ] afforded square planar complexes cis -[PtCl2 (L1)] (1 ) and cis -[PtCl2 (L2)] (2 ) respectively. Both the complexes were characterized by NMR, IR, UV and elemental analysis.2 crystallized in the P 21 / c space group.2 shows greater solution stability than1 in kinetic studies by 1 H NMR. Both1 and2 bind the model nucleobase 9-ethylguanine (9-EtG) and form multiple mono-adducts. Existence of unusual N 7, O 6 chelated guanine bound2 (2e ) was traced. Binding studies of2 with glutathione (GSH) show formation of a mono-adduct cis -[PtCl(L2)SG] (2c ), which transformed within a day to give an aziridinium ion ofL2 (2b ) after loss ofL2 . In vitro cytotoxicity of ligands, complexes and the clinical anticancer drug cisplatin show that2 is the most potent against MCF-7, A549 and MIA PaCa2 exhibiting IC50 values of 12.6 ± 0.8, 18.2 ± 1.8 and 4.2 ± 1.0 μM respectively. The in vitro cytotoxicity of2 against MCF-7, A549 and MIA PaCa2 was also probed in hypoxia and in the presence and absence of added GSH. Even in the presence of excess GSH in hypoxia, 2 exhibits significant cytotoxicity against MIA PaCa2 and MCF-7 with IC50 of 4.4 ± 0.8 and 12.5 ± 1.1 μM respectively. Metal accumulation studies by ICP-MS display greater cellular internalization of2, than1 and cisplatin in MCF-7 cells.2 arrests the cell cycle at sub G1 and G2/M phases in MCF-7 whereas cisplatin exhibits S phase arrest to be dominant with increase in concentration. Complex2 exhibits a change in mitochondrial membrane potential, caspase activity and suggests apoptotic cell death through the intrinsic pathway. Moreover it is encouraging to find that2 also restricts angiogenesis in chick embryo.